FOR A HAPPY DAWN! IS THIS THE LIFE I HAVE ALWAYS WANTED?! A REFLECTION AND SOME PROCEDURES - Iael de Souza; Ryan de Azevedo; Francisco Gleison da Costa Monteiro (Editora da Universidade de Santa Cruz do Sul, 2013)
The documentary "Pro dia Nascer Feliz" (For a Happy Dawn), produced by João Jardim, portrays Brazil's spotted education disparity in silent yet alarming images and concerning testimonials. It discloses this reality and brings about the opportunity for teenagers, teachers, public and private school principals from developed, poor and countryside areas of the country to air the manner they perceive, feel and live this reality. Through the possibilities related in its plot, based upon a Marxian/ Gramscian perspective, we will aim at outlining how we can rethink and reeducate our social educational model by inquirers, considerations and reflections about labor conditions in schools, the education conception and the role teachers play in what is supposed to be taught and learned about the importance of studying, producing knowledge, and the importance and humanizing and emancipatory value of these activities.